- #1

- 13

- 0

Solve for C

I am extremely frustrated and have made countless attempts at this.

I would really appreciate a step by step on this. Thanks.

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Wumbolog
- Start date

- #1

- 13

- 0

Solve for C

I am extremely frustrated and have made countless attempts at this.

I would really appreciate a step by step on this. Thanks.

- #2

Science Advisor

- 5,118

- 2,133

(1) Get all terms with C in them on one side of the equation, and all terms without C on the other side. In other words:

Terms with C = Terms without C

(2) Use the distributive law to write the equation as:

C*(Something without C) = Something else without C

(3) Divide both sides by (Something without C) so you have:

C = (Something else without C) / (Something without C)

Hope this helps.

- #3

Staff Emeritus

Science Advisor

- 9,243

- 1,072

I see an equation comprising 3 terms (one on the left of the equals sign, and two on the right hand side). What does it look like if you multiply each of those 3 terms by L?##V=C-\frac{C-S}{L}N##

Solve for C

- #4

- 13

- 0

##V=C-\frac{C-S}{L}N##

##LV=LC-C-SN##

##\frac{LV}{C}=L-SN##

##C=\frac {L-SN}{LV}##

but apparently this is wrong...

the book gives ##C=\frac{LV-SN}{L-S}##

##LV=LC-C-SN##

##\frac{LV}{C}=L-SN##

##C=\frac {L-SN}{LV}##

but apparently this is wrong...

the book gives ##C=\frac{LV-SN}{L-S}##

Last edited:

- #5

Mentor

- 29,255

- 3,951

[tex]\frac {C-S}{L} N = \frac {(C-S)N}{L}[/tex]

Do you see it now?

Do you see it now?

- #6

- 232

- 10

V = C - N(C-S)/L | * L

LV = LC - NC + NS

LC - NC = LV - NS

C = (LV - NS)/(L-N)

So I have almost the same answer as the book, but I don't even begin to comprehend how an S can ever wind up as part of the demoninator.

- #7

Science Advisor

Homework Helper

Dearly Missed

- 10,704

- 1,721

##LV=LC-C-SN##

##\frac{LV}{C}=L-SN##

##C=\frac {L-SN}{LV}##

but apparently this is wrong...

the book gives ##C=\frac{LV-SN}{L-S}##

You should have ##LV = LC -CN + SN##. Do you see the two errors you made in line 2? Can you see why it is wrong to go from the line

[tex] LV = LC - C - SN[/tex] (which, by itself, is wrong) to

[tex] \frac{LV}{C}=L-SN ?[/tex] Would you say it is correct to go from ##5\times 3 - 3 - 4\times 2## to ##3 \times (5 - 4 \times 2)?## You are claiming these are the same!

- #8

- 13

- 0

Thanks guys I finally got it. And the denominator should have been L-N, my mistake.

Share:

- Replies
- 4

- Views
- 421

- Replies
- 3

- Views
- 420

- Replies
- 8

- Views
- 640

- Replies
- 13

- Views
- 449

- Replies
- 5

- Views
- 995

- Replies
- 2

- Views
- 151

- Replies
- 2

- Views
- 656

- Replies
- 6

- Views
- 512

- Replies
- 6

- Views
- 464

- Replies
- 21

- Views
- 795